Algoritmo genético aplicado à ligas multicomponentes para armazenagem de hidrogênio: implementação de novos parâmetros termodinâmicos - Dias, Victor dos Santos (Universidade Federal de São Carlos, 2024)
Energy demand has increased significantly with the advancement of technology, which is why it is important to study new sources of clean energy. An alternative that has been studied and meets environmental standards is the storage of hydrogen in a solid state in metal hydrides. In recent years, studies have been carried out with single-phase multicomponent alloys with a body-centered cubic structure. Multicomponent alloys can present good hydrogen storage results due to the large compositional field. This is important as hydrogen storage properties directly depend on the composition. Therefore, composition testing is necessary and a cheap and fast method is computational calculations. In this work, two new parameters were added to a previously developed genetic algorithm, the phase transition enthalpy and the plateau enthalpy, to assist in the construction of pressure-temperature-composition diagrams. Nine problems were tested, the first five problems with the same settings as the previous work with the new parameters, later four more problems were tested with new settings of plateau enthalpy and molar mass. The algorithm was able to meet most of the requirements, being tested with and without composition restrictions. However, user experience is necessary to obtain good results.
Genetic algorithm applied to multicomponent alloys for hydrogen storage: Implementation of new thermodynamic parameters
Keywords: Ligas multicomponentes; Armazenamento de hidrogênio; Algoritmo genético; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA::TRANSFORMACAO DE FASES